THE EFFECT OF SUBJECTIVE NORM AND RELIGIOSITY ON PURCHASE INTENTION HALAL FOOD THROUGH STUDENT ATTITUDE IN UNIVERSITY - Elfit Maidah; Heri Pratikto; Titis Shinta Dhewi (International Journal of Economy, Education and Entrepreneurship, 2021)
The halal industry in 2019 became a priority sector developed by the government in Indonesia. The increase in this industry is also expected to encourage the growth of national Islamic finance. The government issued Government Regulation (PP) Number 31 of 2019 concerning the Implementation of Law Number 33 of 2014 concerning the obligation for every business sector engaged in food and beverage products to have a halal certificate. This rule should provide a sense of security to consumers in Indonesia, most of whom are Muslims. This study aims to determine the effect of subjective norms and religiosity on attitude and purchase intention on halal food. The population in this study were Muslim students at 4 State Universities in Malang City. The number of samples in this study was 200. The model and data collection used a questionnaire. The analytical method used is Path analysis. The study results found that both subjective norms and religiosity had a positive and significant effect on Attitude. Then, subjective norms, religiosity, and attitude positively and significantly affect purchase intention. Furthermore, both subjective norms and religiosity positively and significantly affect purchase intention through Attitude. Based on the study results, subjective norms or religiosity directly or indirectly affect intention through Attitude